An Exploratory Study of Sectra Table Visualization Improves the Effectiveness of Emergency Bedside Echocardiography Training. (21st May 2018) - Shi, Di; Walline, Joseph H.; Liu, Jihai; Yu, Xuezhong; Xu, Jun; Song, Priscilla P.; Zhu, Huadong; O'Donnell, John M.
Abstract : Objectives: Echocardiography is an essential tool in emergency medicine, and its training is the most challenging of all types of bedside ultrasound (US) training. This study investigated the effectiveness of the Sectra Table (Sectra AB, Linköping, Sweden), an anatomy visualization and collaboration tool, in improving the quality of echocardiography training for emergency medicine physicians. Methods: We conducted an exploratory prospective observational study from 2015 to 2017 and enrolled 66 trainees who participated in a 2.5‐day bedside US course organized by the emergency department (ED) of Peking Union Medical College Hospital. The study participants underwent 2 different training programs: the first group received standard training, and the second group was trained with Sectra Table experiences integrated into the echocardiography training curriculum. After the training sessions, both groups were evaluated for their hands‐on echocardiography performance. Results: The new training program with the Sectra Table significantly increased trainees' self‐confidence in performing bedside echocardiography. The Sectra Table trainees had a higher performance rating than the trainees in the traditional program, with a mean total assessment score of 40.5 versus 26.5 for traditional training ( P  < .01). The improved performance was evident for all subcategories of echocardiography. The higher performance rating of the Sectra Table trainees was also statistically significant after adjusting for confounders, including prior training experiences, baseline confidence in independently performing ED US examinations, the number of ED US examinations performed, years in ED practice, and physician seniority. Conclusions: Our analysis suggests that integrating the Sectra Table into echocardiography training may improve the effectiveness of training programs.